The Interplay of Electronic Word of Mouth and Social Community in Building Brand Image and Purchase Intention: An Empirical Study on Chinese Heavy Equipment in Indonesia - Bahar, Ferialdy Idhar; ZA, Saida Zainurossalamia; Rahmawati, Heni Rahayu (Indonesian Journal of Advanced Research, 2025)
This study aims to analyze the influence of electronic Word of Mouth (eWOM) and the social community of heavy equipment in Indonesia on the brand image and purchase intention of heavy equipment products from China. This study uses primary quantitative data with questionnaires as a research instrument. The research population is an active member of the heavy equipment social community in Indonesia and has seen reviews about heavy equipment on the internet, social media or online forums. The sampling technique used was the saturated sampling method and a data sample of 253 respondents was obtained. Data collection was carried out using an online questionnaire given directly to respondents through Google Form. The collected data was analyzed using Structural Equation Modelling - Partial Least Square (SEM-PLS) Version 3. The results of the study show that (1) eWOM has a positive and significant effect on brand image. (2) Social community has a positive and significant effect on brand image. (3) eWOM has a positive and significant effect on purchase intention. (4) Social community has a positive and significant effect on purchase intention. (5) Brand image has a positive and significant effect on purchase intention.